A Perception of University Students Regarding the Influence of Social Media on the Academic Performance - Tanveer Nasir; Dr. Syed Abdul Siraj; Dr. Fiza Zia Ul Hannan; Waheed Hussain; Sobia Javed (Journal of Peace, Development and Communication, 2024)
The purpose of this research was to survey the stimulus of social networks on educational performance of scholars inNational University of Science and Technology. Two research questions and three research hypotheses led the study. Uses and gratification theory was used in this deductive research. To accomplish this, Quantitative and the descriptive survey research design was employed. The study focused onNational University of Science and Technology. The simple random sampling technique was utilized to select a sample of 350 students. Likert Type Rating Scale Questionnaire was utilized to assemble data from the students. Descriptive statistics of male and female counts and percentage were utilized to scrutinize the demographic statistics. Research findings revealed that a large number of students inNational University of Science and Technology are addicted to social media. The result from the outcomes shown that social media have negative effects on student’s i.e., lack of privacy, consuming most of their productive time, diverting students from their academic efforts but social media correspondingly have advantages and can be utilized suitably. Students perception regarding social media sites also indicates that social media distract there focus from studies. From virtual communities while planning for an assignment group discussions regarding the class tasks or consumption of social media sites are a way to keep engage while a pupil who has been absent requires to be rationalized on up-to-date academic information.